2022
DOI: 10.3892/etm.2022.11309
|View full text |Cite
|
Sign up to set email alerts
|

Immunological signature of chronic spontaneous urticaria (Review)

Abstract: Chronic urticaria (CU) is a condition characterized by intensely pruritic, edematous, erythematous papules lasting for more than 6 weeks. Over half of the cases have concomitant swelling of deeper tissues, known as angioedema. The socio-economic burden of the disease is significant. Unfortunately, patients with severe CU, refractory to conventional treatment, have limited and expensive therapeutic options. The pathogenesis of CU is not yet completely understood. Therefore, elucidating the pathophysiological me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 97 publications
0
23
1
Order By: Relevance
“…For instance, Zhou et al (2019) (18) proved that elevated IL-4 can promote B cell proliferation and immunoglobulin E production, leading to increased sensitivity to allergens and exacerbation of the disease. Similarly, Huo et al (2020) (19) reported a positive correlation between disease severity and the level of IL-17, as IL-17 can promote the release of in ammatory mediators and chemokines by skin cells, increase in ammation and vascular permeability, and thus exacerbate the formation of wheals and itching symptoms (20,21). Additionally, IL-31 can enhance itching reactions and exacerbate itching symptoms in urticaria patients.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, Zhou et al (2019) (18) proved that elevated IL-4 can promote B cell proliferation and immunoglobulin E production, leading to increased sensitivity to allergens and exacerbation of the disease. Similarly, Huo et al (2020) (19) reported a positive correlation between disease severity and the level of IL-17, as IL-17 can promote the release of in ammatory mediators and chemokines by skin cells, increase in ammation and vascular permeability, and thus exacerbate the formation of wheals and itching symptoms (20,21). Additionally, IL-31 can enhance itching reactions and exacerbate itching symptoms in urticaria patients.…”
Section: Discussionmentioning
confidence: 95%
“…Diagnosing urticaria is easy, but nding its cause is di cult and requires careful examination methods to discover diagnostic clues and rule out serious medical conditions. Several conditions have been found to be related to urticaria symptoms, whereas the term chronic idiopathic urticaria identi es the high percent of conditions in which a pathogenetic factor has not been found [9]. Identifying the cause of urticaria requires ruling out many other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we do not know the exact mechanism of urticaria caused by Cryptosporidium. Anyway, various reasons have been discussed for the cause of urticaria caused by parasitic infections, such as the role of speci c IgE, Th2 cytokine skewing, eosinophil's and coagulation system and nally circulating immune complexes and complement system [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…UAS7 is recommended by the latest chronic urticaria activity guidelines and can be used to assess the number of urticaria and severity of pruritus over 7 days ( Zuberbier et al, 2022 ). Another important pathogenic mechanism of CSU is mediated by the IgE high-affinity receptor (FcεRI) expressed by mast cells ( Dobrican et al, 2022 ). Mast cells are activated upon antigenic stimulation, mediated by IgE, and release multiple mediators, including histamine, to initiate an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%